2022
DOI: 10.1186/s12888-022-04414-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental healthcare-seeking behavior of women in Bangladesh: content analysis of a social media platform

Abstract: Background Mental health remains a highly stigmatized area of healthcare, and people often conceal their concerns rather than seek assistance or treatment. The Women Support Initiative Forum (WSIF) is a social media platform established in 2018 to provide expert and peer-led psychosocial support services to women of all ages in Bangladesh. The anonymous nature of the forum means that mental health concerns can be aired without fear of identification. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Of the 64 (47.8%) studies using the content analysis methodology, 35 (54.7%) [ 40 , 45 , 48 , 49 , 64 , 70 , 72 , 73 , 76 , 77 ,​ 79 , 80 , 91 , 93 , 95 , 97 , 105 , 108 , 118 , 125 , 128 , 129 , 131 , 132 , 136 ,​ 138 , 149 , 150 , 153 - 155 , 159 , 161 , 162 , 166 ] used general qualitative content analysis to classify and analyze online social media information. In logic application, 5 (7.8%) studies [ 78 , 83 , 100 , 109 , 152 ] used inductive content analysis to analyze the collected information and to ensure that the codes arose from the data themselves rather than being predefined. In addition, 3 (4.7%) studies [ 44 , 92 , 107 ] used deductive content analysis to apply coding strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 64 (47.8%) studies using the content analysis methodology, 35 (54.7%) [ 40 , 45 , 48 , 49 , 64 , 70 , 72 , 73 , 76 , 77 ,​ 79 , 80 , 91 , 93 , 95 , 97 , 105 , 108 , 118 , 125 , 128 , 129 , 131 , 132 , 136 ,​ 138 , 149 , 150 , 153 - 155 , 159 , 161 , 162 , 166 ] used general qualitative content analysis to classify and analyze online social media information. In logic application, 5 (7.8%) studies [ 78 , 83 , 100 , 109 , 152 ] used inductive content analysis to analyze the collected information and to ensure that the codes arose from the data themselves rather than being predefined. In addition, 3 (4.7%) studies [ 44 , 92 , 107 ] used deductive content analysis to apply coding strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the studies [ 98 , 146 , 156 , 165 ] improved analysis methods to achieve a higher accuracy in predicting the trends of information on the network and applied them to clinical practice. Other studies [ 55 , 60 , 75 , 84 , 85 , 100 , 123 , 147 ] identified general characteristics and development trends of specific health service content through epidemiological investigation methods. For example, after reviewing the posts related to COVID-19 on Chinese social media platforms, Zhang et al [ 147 ] found that the COVID-19 information on Chinese social media is characterized by gradual progress and repeated fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 64 (47.8%) studies using the content analysis methodology, 35 (54.7%) [40,45,48,49,64,70,72,73,76,77,79,80,91,93,95,97,105,108,118,125,128,129,131,132,136,138,149,150,[153][154][155]159,161,162,166] used general qualitative content analysis to classify and analyze online social media information. In logic application, 5 (7.8%) studies [78,83,100,109,152] used inductive content analysis to analyze the collected information and to ensure that the codes arose from the data themselves rather than being predefined. In addition, 3 (4.7%) studies [44,92,107] used deductive content analysis to apply coding strategies.…”
Section: Content Analysis Methodologymentioning
confidence: 99%
“…We can see clear evidence from the National Mental Health Survey 2019 that men suffer from anxiety (4%) and women suffer (5.4%); in terms of depression, men suffer (5.4%); women suffer (7.9%); in terms of any mental health disorder, men suffer (15.7%); and women suffer (21.5%) (Mental-Health-Survey-Report.Pdf, n.d.). We can observe the reasons behind the vulnerability of women through a study (Koly et al, 2022) conducted in Bangladesh focused on the analysis of social media platform. It is seen that women cited as reasons for their mental health issues a lack of physical intimacy in their relationships, abnormal sexual fantasies, pornography addiction, and in delity by their male partners.…”
Section: Vulnerabilitymentioning
confidence: 99%